Curriculum Reform and the Implementation of Independent Learning Policies in Indonesian Schools - Andri Cahyo Purnomo; Sahal Hanafi; Ali Anhar Syi’bul Huda; Muslim Muslim; Samsul Arifin (Journal of Contemporary Pedagogy and Learning Science, 2026)
This study examines curriculum reform and the implementation of Independent Learning (Merdeka Belajar) policies in Indonesian schools through a non-empirical design combining systematic narrative literature review and policy document analysis. Drawing on peer-reviewed studies and official policy materials, the analysis investigates how governance structures, pedagogical translation, and institutional capacity shape school-level enactment of the Independent Curriculum (Kurikulum Merdeka). Findings indicate that reform outcomes are strongly mediated by leadership competence, professional development ecosystems, and resource distribution, producing significant variation between schools and regions. Teacher agency emerges as the primary mechanism through which autonomy-oriented policy ideals are operationalized, yet interpretive ambiguity and accountability pressures frequently redirect implementation toward procedural compliance. Differentiated learning and project-based orientations are widely positioned as core pedagogical principles, but they remain fragile in contexts lacking sustained institutional support and coherent operational routines. The synthesis further shows that autonomy-based reform can intensify systemic inequity when capacity conditions are uneven, enabling innovation in well-resourced schools while constraining meaningful enactment in disadvantaged settings. The study contributes a multi-level interpretive framework for understanding curriculum reform as capacity-mediated policy enactment.